Association between General Anesthesia and Root Canal Treatment Outcomes in Patients with Mental Disability: A Retrospective Cohort Study - Guan-Yu Chen, - (MDPI, 2022)
In the population of individuals with a disability, mental illness patients can be uncooperative during dental treatment; thus, general anesthesia has been widely applied during dental procedures. This study aims to investigate the association between general anesthesia and the outcomes of root canal treatment in patients with disability. Teeth treatment records of patients with disability from Kaohsiung Medical University Hospital Research Database and electronic database from January 2005 to December 2018 were used in this retrospective cohort study. The authors conducted analysis comparing root canal treatment outcomes under general anesthesia and non-general anesthesia, indicated by endodontic re-treatment or post-treatment teeth extraction. Over the 9-year follow-up period, root canal treatment outcomes representing a cumulative survival rate of 87.68% and 74.51% in the general anesthesia group and non-general anesthesia group, respectively, were found. After adjustment for potential confounders, the teeth with general anesthesia showed a substantially and significantly reduced HR of root canal treatment failure at 0.24 (95% confidence interval, 0.12 to 0.49). Our study supported the notion that root canal treatment with general anesthesia may entail substantial reduction of treatment failure in patients with disability.